Understanding the material safety data sheet - Skoglund, L. G., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes what the Material Safety Data Sheet is, how it is to be used, and covers the sections of the MSDS.
CEPEP 5/00, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Materials -- Safety measures; Hazardous substances -- Safety measures